Fashion Inspired by Architecture: The Interrelationship between Mashrabiya and Fashion World - Özsavaş Akçay, Ayten; Alothman, Hiba (Journal of History Culture and Art Research, 2018)
The relationship between architecture and fashion fields have received many studies. Some researches have considered them as parallel worlds, while others have proven that the link is an interrelationship. Generally, architecture and fashion have many common sources: art, science, and technology. This makes them sometimes close worlds, and in many other cases, they are mixed. However, it is wise to assume that the best situation when one field becomes a source to another, and they support each other within a logical visible relationship. Architecture gives inspiration to fashion, per contra fashion achieves notability for an architectural figure or element. Mashrabiya (The traditional Arab oriel window that works as an environmental architectural element) has entered into fashion field through one of the new approaches of the heritage restoration movement. This approach has presented unique fashion shows and unparalleled jewellery designs, while made Mashrabiya a popular name in non-architectural surroundings. While the environmental functions of Mashrabiya are used in many contemporary projects without acknowledging its original name "Mashrabiya". Moreover, other projects dealt with it using a new name like ‘geometric panels', fashion has maintained the authenticity of the name and its orientalism. This article tries to show that Mashrabiya is one of the architectural element which gives inspiration to the fashion world. The article also presents examples of fashion and jewellery design inspired from the Mashrabiya element.